KP177R-based visual assay integrating RPA and CRISPR/Cas12a for the detection of African swine fever virus - Luan, Haorui; Wang, Shujuan; Ju, Lin; Liu, Tong; Shi, Haoyue; Ge, Shengqiang; Jiang, Shijin; Wu, Jiaqiang; Peng, Jun (Frontiers in Immunology, 2024)
Introduction Early detection of the virus in the environment or in infected pigs is a critical step to stop African swine fever virus (ASFV) transmission. The p22 protein encoded by ASFV KP177R gene has been shown to have no effect on viral replication and virulence and can serve as a molecular marker for distinguishing field virus strains from future candidate KP177R deletion vaccine strains. Methods This study established an ASFV detection assay specific for the highly conserved ASFV KP177R gene based on recombinase polymerase amplification (RPA) and the CRISPR/Cas12 reaction system. The KP177R gene served as the initial template for the RPA reaction to generate amplicons, which were recognized by guide RNA to activate the trans-cleavage activity of Cas12a protein, thereby leading to non-specific cleavage of single-stranded DNA as well as corresponding color reaction. The viral detection in this assay could be determined by visualizing the results of fluorescence or lateral flow dipstick (LFD) biotin blotting for color development, and was respectively referred to as fluorescein-labeled RPA-CRISPR/Cas12a and biotin-labeled LFD RPA-CRISPR/Cas12a. The clinical samples were simultaneously subjected to the aforementioned assay, while real-time quantitative PCR (RT-qPCR) was employed as a control for determining the diagnostic concordance rate between both assays. Results The results showed that fluorescein- and biotin-labeled LFD KP177R RPA-CRISPR/Cas12a assays specifically detected ASFV, did not cross-react with other swine pathogens including PCV2, PEDV, PDCoV, and PRV. The detection assay established in this study had a limit of detection (LOD) of 6.8 copies/μL, and both assays were completed in 30 min. The KP177R RPA-CRISPR/Cas12a assay demonstrated a diagnostic coincidence rate of 100% and a kappa value of 1.000 (p < 0.001), with six out of ten clinical samples testing positive for ASFV using both KP177R RPA-CRISPR/Cas12a and RT-qPCR, while four samples tested negative in both assays. Discussion The rapid, sensitive and visual detection assay for ASFV developed in this study is suitable for field application in swine farms, particularly for future differentiation of field virus strains from candidate KP177R gene-deleted ASFV vaccines, which may be a valuable screening tool for ASF eradication.